Identifying policy approaches to build social–ecological resilience in marine fisheries with differing capacities and contexts. (18th June 2021) - Kleisner, Kristin M; Ojea, Elena; Battista, Willow; Burden, Merrick; Cunningham, Erica; Fujita, Rod; Karr, Kendra; Amorós, Samuel; Mason, Julia; Rader, Doug; Rovegno, Nicolas; Thomas-Smyth, Alice
Abstract: Fisheries are critically important for nutrition, food security, livelihoods, and culture of hundreds of millions of people globally. As climate impacts on ocean ecosystems increase, policy-makers are asking critical questions about how to implement reforms at local and national levels to reach goals around improving performance of management systems, sustainability, equity, and resilience to climate change. These goals can be achieved by enhancing the structure, function, and biodiversity of marine ecosystems as climate change proceeds, together with adaptive, sustainable management. However, resource, technical, and governance capacities vary widely across management systems. These capacities will determine, in part, the best policy approaches to build resilience and overcome systemic challenges to equity and sustainability to stressors such as climate change. To illuminate how fisheries resilience can be improved within the constraints imposed by these capacity limits, we present case studies from Myanmar, Belize, Peru, and Iceland, which offer a spectrum of capacity conditions to explore social–ecological resilience challenges and solutions. Using a set of nine social–ecological resilience criteria, we examine each system's attributes that may confer or undermine resilience and explore interactions between them. We use this assessment to identify policy approaches that can help build resilience in each particular context.